Src homology 3 domain binding kinase 1 protects against hepatic steatosis and insulin resistance through the Nur77–FGF21 pathway. Issue 1 (22nd January 2023) - Ahuja, Palak; Bi, Xinyi; Ng, Chun Fai; Tse, Margaret Chui Ling; Hang, Miaojia; Pang, Brian Pak Shing; Iu, Elsie Chit Yu; Chan, Wing Suen; Ooi, Xin Ci; Sun, Anqi; Herlea‐Pana, Oana; Liu, Zhixue; et al.
Abstract : Background and Aims: Metabolism in the liver is dysregulated in obesity, contributing to various health problems including steatosis and insulin resistance. While the pathogenesis of lipid accumulation has been extensively studied, the protective mechanism against lipid challenge in the liver remains unclear. Here, we report that Src homology 3 domain binding kinase 1 (SBK1) is a regulator of hepatic lipid metabolism and systemic insulin sensitivity in response to obesity. Approach and Results: Enhanced Sbk1 expression was found in the liver of high‐fat diet (HFD)–induced obese mice and fatty acid (FA)–challenged hepatocytes. SBK1 knockdown in mouse liver cells augmented FA uptake and lipid accumulation. Similarly, liver‐specific SBK1 knockout ( Lsko ) mice displayed more severe hepatosteatosis and higher expression of genes in FA uptake and lipogenesis than the Flox/Flox ( Fl/Fl ) control mice when fed the HFD. The HFD‐fed Lsko mice also showed symptoms of hyperglycemia, poor systemic glucose tolerance, and lower insulin sensitivity than the Fl/Fl mice. On the other hand, hepatic Sbk1 overexpression alleviated the high‐fructose diet–induced hepatosteatosis, hyperlipidemia, and hyperglycemia in mice. White adipose tissue browning was also observed in hepatic SBK1 ‐overexpressed mice. Moreover, we found that SBK1 was a positive regulator of FGF21 in the liver during energy surplus conditions. Mechanistically, SBK1 phosphorylates the orphan nuclear receptor 4A1 (Nur77) on serine 344 to promote hepatic FGF21 expression and inhibit the transcription of genes involved in lipid anabolism. Conclusions: Collectively, our data suggest that SBK1 is a regulator of the metabolic adaption against obesity through the Nur77–FGF21 pathway. Abstract :